The oldest record of Ceratophrys (Anura, Ceratophryidae) from the Late Miocene of central Argentina - Nicoli, Laura (2017)
Ceratophrys is the most diverse and widely distributed genus of Ceratophryidae, the clade of South American horned frogs. It includes eight extant species, the relationships of most of which have been recently studied on the basis of molecular information (Faivovich et al., 2014). Additionally, numerous remains from the Cenozoic of South America were attributed to this genus and even a series of fossil species have been recognized (see Faivovich et al., 2014; Nicoli, 2014; Scanferla and Agnolin, 2015). Several of these assignations, however, are problematic (see Faivovich et al., 2014; Nicoli, 2014) and are being revisited (Nicoli, in prep.). One of the questionable aspects of this record is that only in a few cases the taxonomic assignations were properly discussed, that is, establishing the presence of the synapomorphies (or possible synapomorphies) of Ceratophrys in the fossil remains. In addition, in most cases the stratigraphic provenance of the fossils and the age estimates of the bearing levels are not well-known, which prevents the use of fossils as calibration points in molecular clock analyses (Faivovich et al., 2014).